1980
DOI: 10.1051/rnd:19801001
|View full text |Cite
|
Sign up to set email alerts
|

Development and initiation of sperm motility in the hamster epididymis

Abstract: Summary. Hamster Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Two compounds found in epididymal fluid can influence the motility of proximal caput spermatozoa in vitro, L-carnitine (Hinton et al, 1981) and acidic epididymal glycoprotein (AEG), the latter probably nonspecifically (Pholpramool et al, 1983). Another factor, forward motility protein (FMP), was implicated in the change in caput epididymal spermatozoan motility from a circling to a progressive motion in bulls (Acott et al, 1983) and hamsters (Kann & Serres, 1980;Serres & Kann, 1984) in vitro. In the hamster, retroflexion of the head brought about by such motility induction may be controlled by sulfydryl oxidation (Cornwall et al, 1986(Cornwall et al, , 1988.…”
Section: Discussionmentioning
confidence: 99%
“…Two compounds found in epididymal fluid can influence the motility of proximal caput spermatozoa in vitro, L-carnitine (Hinton et al, 1981) and acidic epididymal glycoprotein (AEG), the latter probably nonspecifically (Pholpramool et al, 1983). Another factor, forward motility protein (FMP), was implicated in the change in caput epididymal spermatozoan motility from a circling to a progressive motion in bulls (Acott et al, 1983) and hamsters (Kann & Serres, 1980;Serres & Kann, 1984) in vitro. In the hamster, retroflexion of the head brought about by such motility induction may be controlled by sulfydryl oxidation (Cornwall et al, 1986(Cornwall et al, , 1988.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the efficacy and other characteristics of these proteins from the point of motility regulation. Several investigators have demonstrated that in vitro initiation of forward motility in the immature caputepididymal sperm requires four exogenous parameters: theophylline, an EP protein, bicarbonate, and alkaline pH Kann and Serres, 1980;Cornwall et al, 1986;Majumder, 1996a,b, 1998). Bicarbonate works by elevating the intrasperm level of cyclic AMP (Okamura et al, 1985;Tajima et al, 1987;Rojas et al, 1992;Jaiswal and Majumder, 1998) whereas theophylline enhances sperm level of cyclic AMP but by inhibiting cyclic phosphodiesterase Jaiswal and Majumder, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Hoskins et al (1978) has developed an in vitro method for the initiation of forward motility in the immature bovine caputepididymal spermatozoa when incubated in presence of theophylline and epididymal plasma (EP)/seminal plasma. These and other studies (Kann and Serres, 1980;Pinto et al, 1984;Cornwall et al, 1986;Majumder, 1996a,b, 1998) implicated that extra cellular bicarbonate, elevated level of intrasperm cyclic AMP and pH are important parameters for the induction of flagellar motility. EP has been shown to possess an undefined protein factor, which is necessary for the initiation of sperm motility (Pinto et al, 1984).…”
mentioning
confidence: 91%
“…The maturation of hamster spermatozoa also occurs more distally than that of rat spermatozoa (see Dacheux & Paquignon, 1980). In both species the decline in enzyme activity occurred in the region of the epididymis where the spermatozoa become capable of progressive motility (Hinton, Dott & Setchell, 1979 ; Kann & Serres, 1980) and where the concentration of carnitine in the lumen of the duct increases sharply (Hinton, Snoswell & Setchell, 1979). These changes precede the acquisition of fertility by the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%